Respon Medis Terpadu dan Pelayanan Kesehatan Darurat Pasca Bencana Banjir di Kecamatan Barus Kabupaten Tapanuli Tengah - Yaltafit Jeem; Utami Utami; Edi Fitriyanto; Riana Rahmawati; Syaefudin Ali Akhmad; Fit Anastyo; Mellody Yudhashinta Putri Cahyono; Annisa Sofiana; Alfan Nur Ashar; Rianti Maharani; Muhammad Ihsan Mumtaz Ghifari; Ikhwan Faqih Atsani; Muhammad Aflah; Bayu Gentari Rahman; Ridwansyah Ridwansyah; Yulianto Yulianto; Agus Prastyo; Rifki Hidayat (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Floods and landslides in Central Tapanuli Regency have paralyzed health infrastructure and increased the risk of infectious diseases among vulnerable groups. This community service aims to restore access to health services and prevent outbreaks through a comprehensive medical response. The method utilized a collaborative Comprehensive Emergency Response approach, including curative medical services (mobile clinic), pharmaceutical logistics distribution, nutritional intervention, and psychosocial support. The activities were conducted in the working area of Barus Public Health Center (Puskesmas) in December 2025. The results showed that the medical team successfully treated over 245 patients, predominantly suffering from URI and dermatitis, and performed circumcision for 12 children. In addition to medical services, 38,802 units of medicine, 1,538 units of medical equipment, and 300 packages of supplementary food for pregnant women and toddlers were distributed. This intervention not only reduced physical morbidity and psychological trauma but also revitalized the functionality of the local Puskesmas through logistical stock support. It is concluded that the integration of mobile medical services and supply chain strengthening is effective in mitigating the impact of disasters in isolated areas.